UNIVERSITY NOTES. (The Accounting Review, 1928)
Abstract The article presents various developments in several universities related to the field of accounting in the U.S. Professor Henry Braywn Gardner, professor of political economics in the Brown University, will retire in June 1928, after 40 years as head of the department of economics, and professor James P. Adams has been appointed chairman of the department, effective with the academic year 1928-1929. According to another information Ralph Eastman Badger, formerly associate professor of economics returns as professor of economics after two years as investment counselor for the estate of Frank A. Sayles. The University of Chicago professor J.O. Mckinsey's professional work as organization councilor and accountant has forced him to reduce his university work to the giving of two courses, business organization and business policies. Professor W.S. Krebs of Washington University will offer a course in accounting theory in the first term of the summer quarter. Professor H.C. Daines is serving as chairman of an advisory commission, which is revising the accounting curriculum of the Chicago Central College of Commerce, an institution serving employed men.